Kontrol Temperatur dan Kelembapan pada Ingkubator Bayi Menggunakan Platform Antares - Pratama, Kurniawan Maulana; Mahmudah, Norma; Praharsena, Bayu (Techno Bahari, 2024)
The condition of premature birth is a condition where a baby needs an incubator to maintain the baby's body temperature, because premature babies do not have many weaknesses to regulate body temperature so that they are prone to hypothermia. Setting the temperature and humidity in the baby incubator is an important aspect of caring for premature babies. The use of baby incubators in hospitals requires a high cost of up to Rp. 500,000 per night, even though premature babies need care in an incubator for up to one month, therefore a tool is needed to control humidity and temperature based on the Internet of Things. Control the humidity and temperature of the air used in the patient's home using a microcontroller where the microcontroller will detect the humidity and temperature inside the baby and the temperature measurement results can be viewed via the internet of things which can display temperature and humidity reading data remotely. The results of the comparison between LYNX32 and the platform between the displayed temperature and humidity values have an error of 0%. The Antares platform display displays temperature and humidity data in real time and has historical data that can be downloaded via the Antares platform, making it easier for nurses to monitor conditions.